Foot and Ankle Pain and Injuries in Elite Adult Irish Dancers - Cahalan, R.; Purtill, H.; O'Sullivan, Peter; O'Sullivan, Keiran (Science and Medicine, 2014)
Background: In Irish dance, the foot and ankle are the structures most commonly affected by pain and injury, but there is scant research examining the potential factors placing Irish dancers at risk of sustaining pain and injury in the foot and ankle. Study Design: An observational study examining the factors linked to pain and injury in the foot and ankle in elite adult Irish dancers. Methods: The biopsychosocial characteristics of 29 subjects with no previous pain and injury in the foot and ankle were compared to 53 subjects who cited the foot and ankle as their most troublesome bodily area. These 82 subjects were professional, competitive, and student Irish dancers, of both sexes aged 18 years or older, and were allocated to "never troublesome" (NT) and "most troublesome" (MT) groups, respectively. Results: Factors found to be statistically significant for membership of the MT group included female gender (p=0.004), greater gastrocnemius flexibility (p=0.021), better single leg balance (p=0.019), and a higher number of endurance jumps (p=0.009). The MT group reported more severe levels of day-to-day pain (p=0.038), greater bothersomeness of daily pain (p=0.005), more subjective health complaints (p=0.024), more psychological complaints (p=0.030), and a greater number of bodily areas experiencing pain and injury (p=0.025). Conclusions: Pain and injury in the foot and ankle in elite adult Irish dancers is commonplace and comparable to levels of injury in other elite forms of dance. A complex mix of biopsychosocial factors is associated with pain and injury in the foot and ankle in this cohort.